Instant‐quality fluorescence in‐situ hybridization as a new tool for HER2 testing in breast cancer: a comparative study. Issue 2 (1st October 2013) - Franchet, Camille; Filleron, Thomas; Cayre, Anne; Mounié, Eveline; Penault‐Llorca, Frédérique; Jacquemier, Jocelyne; MacGrogan, Gaëtan; Arnould, Laurent; Lacroix‐Triki, Magali
<x xml:space="preserve">Abstract</x> Aims HER2 instant‐quality fluorescence in‐situ hybridization (IQFISH) is a new fluorescence in‐situ hybridization (FISH) assay developed with a non‐toxic buffer that reduces the hybridization time to 1–2 h, enabling a turnaround time of 3 h 30 min from dewax to counting. The aim of this study was to compare assessment of HER2 status using IQFISH and assessment using standard FISH. Methods and results We selected 160 breast cancer samples according to their HER2 status as determined by immunohistochemistry (IHC) in a retrospective multicentre cohort (40 cases in each scoring category, i.e. 0/1+/2+/3+). Each participating site (n = 5) constructed its tissue microarray (TMA) of 32 archival cases and sent it to the central site (site 1). HER2 IHC, HER2 FISH and HER2 IQFISH were performed blindly at site 1. IQFISH provided excellent quality signals without any background staining, thus allowing excellent reading conditions even on TMA. Statistical analysis showed almost perfect agreement between IQFISH and FISH (99.3%, κ = 0.98). The only discordant case was an equivocal one with an HER2/CEP17 ratio near the ASCO/CAP cut‐off. Conclusions The highly concordant data support IQFISH as a useful alternative to FISH, allowing reliable assessment of HER2 status. Use of this method could lead to reporting of HER status to the oncologist within a day.